The Primitive Tribal Groups of Kerala: A Situational Appraisal - Seetha Kakkoth (Stud. Tribes Tribals, 3(1): 47-55 (2005), 2005)
Kerala is a homeland of a number of tribal communities. Thirty-six communities are listed in the Scheduled Tribes list of the State. Of them five tribal communities viz., Koraga, Kattunayakan, Cholanaickan, Kurumbar and Kadar have been categorized as Primitive Tribal Groups (PTGs) by the Government of India in 1976, based on the criteria of pre-agricultural level of technology, less than five per cent literacy, marginal or stagnant rate of growth etc. Socio-culturally, techno-economically, eco-demographically, educationally etc., these communities vary from one another and lay at different stages of development. The welfare programmes so far implemented haven't focused on the felt needs of the communities, hence could not yield the desired results. Thus, for the overall development of these communities, the study recommends tribe-specific action with the active participation of the community members